Scotland, Highlands & Islands : handbook. - Murphy, Alan, ....- (Bath : Footprint, 2011)
When the rain stops falling and the mist clears there is no more beautiful place on Earth than the Scottish Highlands and Islands, Europe's last great wilderness. Hailed as the best guidebook to the region, Footprint's 5th edition of Scotland Highlands & Islands gives you everything you need to get the most out of your trip; the loveliest glens and lochs, the spookiest places, the most evocative castles and most glorious beaches are all here, along with the best places to stay and eat and where to enjoy a wee dram of your favourite malt whisky.
Keywords: Schotland -- Reisgidsen